Nostromo : a tale of the seaboard - Conrad, Joseph, 1857-1924 (Oxford world's classics (Oxford University Press), 2007)
One of the greatest political novels in any language, Nostromo enacts the establishment of modern capitalism in a remote South American province locked between the Andes and the Pacific. This edition offers new insights into Conrad's masterpiece. - ;'I have heard no end of tales of his strength, his audacity, his fidelity ... incorruptible! It is indeed a name of honour for the Capataz of the Cargadores of Sulaco.'. One of the greatest political novels in any language, Nostromo enacts the establishment of modern capitalism in a remote South American province locked between the Andes and the Paci.